Wound-related pain during wound care among orthopedic patients at Hospital Universiti Sains Malaysia - Hanafi, Nursyariena (Pusat Pengajian Sains Kesihatan, 2014)
Management of pain at dressing changes still appears to be an issue that is poorly managed in the clinical practice, causing the patient considerable distress. The aim of this study is to determine the wound-related pain among postoperative orthopedics patients at Hospital Universiti Sains Malaysia (Hospital USM). This cross sectional study also examined the difference level of pain with gender and difference level of pain with location of wound. Sixty hospitalized patients in the three orthopedic wards at Hospital USM were recruited in this study using purposive sampling. Data were collected from January to March 2014 using assessment tools and analyzed using SPSS version 20.0 for frequency, percentage, mean, standard deviation and p-value. The orthopedic patients reported their level of pain during wound dressing as being moderate pain (M= 4.6, SD= 1.15). 23 (38.3%) patients reported pain during dressing change. The study found that there is no significant difference between level of pain and location of wound (p= 0.08). In addition, there is a significant different between level of pain and gender (p= 0.001). Thus, nurses should identify the wound-related pain during wound dressing among orthopedics patients to improve the management of pain as well as quality of nursing care in order to prevent further complications to the patients.